Biodiesel production from lipids of municipal sewage sludge by direct methanol transesterification. Issue 8 (18th April 2017) - Demirbas, Ayhan; Bamufleh, Hisham S.; Edris, Gaber; Al-Sasi, Basil Omar
ABSTRACT: Municipal sewage sludge (MSS) is a biowaste formed during wastewater treatment and the sewage sludge can be obtained from industrial wastewater treatment system. The sewage sludge contains a variety of organic and inorganic compounds, mainly lipids, proteins, sugars, detergents, and phenols. The MSS contains a significant amount of lipid fraction characterized as oils, greases, fats, and long-chain fatty acids. The average yield of methyl esters from the MSS lipids is 24%. The total average of saturated fatty acids reaches as high as 55.0%. Palmitic acid (37.5%) was the major saturated fatty acid, followed by stearic acid (12.0%). Oleic acid (29.0%) was the major unsaturated fatty acid, followed by linoleic acid (6.2%). The optimum production of biodiesel is faced with huge challenges. The main challenges are collecting and drying the sludge, separating lipids, microbial processing, optimum production of biodiesel and product separation, soap formation, maintaining product quality, bioreactor design, economics of biodiesel production, and regulatory concerns. Wet MSS samples were used in the experiments. Drying cost is 41.5% of the total cost of biodiesel from the sludge. The increase in water content does not affect methyl ester (biodiesel) efficiency in supercritical methanol transesterification (SCMT). The increase in free fatty acid content does not affect methyl ester efficiency in SCMT.